Microstructural characterization of aluminum powder liquid coating on IN 738 superalloy - Visuttipitukul, Patama; Limvanutpong, Nuntiya; Krongtong, Viyaporn; Wangyao, Panyawat (Journal of Metals, Materials and Minerals, 2017)
The powder liquid coating method was proposed for aluminizing of nickel-based superalloy grade IN738 in this study. Slurries for the coating consisted of aluminum and alumina (Al2O3) powder with various weight ratios in the range from 3:7 to 10:0. The slurries were pasted onto the IN738 specimens, which were subsequently dried and heated under argon atmosphere. Macrostructures of coated samples were observed. Surface and cross-sectional microstructures were studied by OM and SEM. Qualitative analysis and composition mapping were analyzed by EDS. Phase identification of coated surface was done by GIXD, at the incident angle of 2 degrees. The results showed inhomogeneous formation of Ni2Al3 on the coated surface. The Ni2Al3 phase had the structure of dispersed nodular islands and of thin discontinuous layer on flat area. Size and amount of nodular islands were larger when the ratio of Al:Al2O3 increased. Therefore, the amount of Ni2Al3 formation was increased with the ratio of Al:Al2O3. These nodular islands were formed due to the low wettability of liquid aluminum on nickel surface. Some aluminum oxide and chromium oxide were found in coexistence with Ni2Al3.